2016
DOI: 10.1037/pac0000154
|View full text |Cite
|
Sign up to set email alerts
|

Soldiers perpetrating or witnessing acts of humiliation: A community-based random sample study design.

Abstract: Where soldiering activities include administrating civilians, humiliating behaviors may become commonplace. Our goal was to assess frequency and correlates of Israeli soldiers witnessing or committing humiliating behaviors toward the civilian Palestinian population (CPP). Results indicate that among veterans, 17.4% of men and 10.2% of women (n ϭ 151) had either participated or witnessed the degradation of CPP. Posttraumatic stress, dissociation, previous aggression against CPP, combat experience against Palest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Military raids and incursions are an integral part of these duties, and may include entry into houses suspected of harboring terrorists. Thus, while confronting door‐to‐door fighting, attention sometimes needs to be paid to other, nonterrorist, family members (Gelkopf, Berger, & Roe, ). Indeed, qualitative studies performed in Israel have shown that military service in the occupied territories has led to significant traumatization (Maoz, ) and "moral trauma" (Blachar, ).…”
Section: Introductionmentioning
confidence: 99%
“…Military raids and incursions are an integral part of these duties, and may include entry into houses suspected of harboring terrorists. Thus, while confronting door‐to‐door fighting, attention sometimes needs to be paid to other, nonterrorist, family members (Gelkopf, Berger, & Roe, ). Indeed, qualitative studies performed in Israel have shown that military service in the occupied territories has led to significant traumatization (Maoz, ) and "moral trauma" (Blachar, ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, investigating PMIEs and their outcomes among IDF soldiers offers a genuinely unusual challenge, given their dual military roles: (a) guarding Israel's international borders and involvement in typical armed conflict, and (b) executing border security and policing roles, such as operating checkpoints, patrols, arresting civilians, LEVI-BELZ, LEVINSTEIN, AND ZERACH and ambush assignments in the West Bank (requiring close contact with civilians at different levels of friction; Levi-Belz et al, 2022). Such potentially conflicting military roles may expose soldiers to ethical challenges, particularly given the contact with civilian women and children (Gelkopf et al, 2016).…”
Section: The Present Studymentioning
confidence: 99%
“…Israeli Defense Forces (IDF) combatants' routine includes: peacekeeping missions in the West Bank populated with Palestinian inhabitants (alongside the traditional missions of securing Israel's borders and participating in traditional warfare). Thus, this is a highly relevant population, as their missions may expose them to ethical challenges, when it is more difficult to decide on the most prudent way to react toward noncombatants (or potential combatants), despite battlefield ethics training and the rules of engagement (Gelkopf et al, 2016).…”
Section: The Present Studymentioning
confidence: 99%